THE EFFECTIVENESS OF USING POPULAR SONGS TO INCREASE STUDENTS’ VOCABULARY MASTERY ON THE SECOND GRADE STUDENTS OF SMK KRISTEN TOMBATU - Ridel Rio Rambembuoch; Noldy Pelenkahu; Nurmin Samola (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study was to investigate whether there is a significant difference in vocabulary skills between grade 11 students taught using popular songs and those taught without popular songs. . In this study, 15 students from XI AKP participated as an experimental class and 16 students from XI TKJ participated as a control class. Data were collected using a vocabulary test. Through trial and error, I found that her 20 items on the test were valid with a confidence level of 0.88. These items were administered to her two groups as pre- and post-tests. The results of the study show that there is a significant difference in students' vocabulary proficiency between the experimental and control classes. The mean posttest score for the experimental class is 66, and the mean score for the control class is 41.25. The t-test results show that the t-observation (5.053) is higher than the t-table (2.045). In summary, using popular songs can improve students' vocabulary. Encourage teachers to use popular songs as a medium for teaching vocabulary to students.